Gross motor deficits among preschool children with mental retardation who have physical handicaps - Villareal, Joan G. (2005)
A three-part researcher-designed questionnaire was used in the attempt to characterize the implementation of the DepEd curriculum for gross motor skills and the P.E. programs of different private SPED schools. Seven learning areas under Gross motor skills curriculum which address the gross motor skills of the students were attitudes, body image, laterality and directionality, prevocational skills, non-locomotor skills, locomotor skills, recreational skills and perceptual motor skills. Teaching approaches like behavior modification, positive reinforcement, repetition, task analysis, kinesthesis, practice trials and drills, physical prompting, verbal feedback, visual feedback, demonstration, use of reward, one-on-one, sensory integration, neurodevelopmental techniques,and integration of physical therapy can be used by the teacher for special learners who are honing their motor skills.